2001
DOI: 10.1074/jbc.m100379200
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Phenotype of Heparan Sulfate in theHs2st−/− Mutant Mouse

Abstract: Heparan sulfate (HS) is a co-receptor for a number of growth factors, morphogens, and adhesion proteins. HS biosynthetic modifications may determine the strength and outcome of HS-ligand interactions. We previously described the phenotype of mice with a gene-trap mutation in Hs2st, encoding the key HS 2-O-sulfotransferase enzyme in HS polymer modification. In contrast to the early developmental failure of embryos lacking HS, the onset of abnormalities in the Hs2st ؊/؊ mice occurs only after midgestation, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 40 publications
(42 reference statements)
9
154
2
Order By: Relevance
“…Surprisingly, the HS2ST-deficient mouse cells mounted an apparently normal signaling response to several growth factors despite the fact that at least some growth factors require a 2-O-sulfate group for their binding to HS. Compensatory increases in N -and 6-O-sulfation were observed for the HS chains of these cells (86) and may explain why a wide range of tissues except the kidney are affected only mildly (85). These results appear to suggest that a hitherto unknown biosynthetic mechanism exists, by which a structurally unusual HS is synthesized in the mutant cells to fulfill some, but not all, of functions of normal HS.…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 60%
“…Surprisingly, the HS2ST-deficient mouse cells mounted an apparently normal signaling response to several growth factors despite the fact that at least some growth factors require a 2-O-sulfate group for their binding to HS. Compensatory increases in N -and 6-O-sulfation were observed for the HS chains of these cells (86) and may explain why a wide range of tissues except the kidney are affected only mildly (85). These results appear to suggest that a hitherto unknown biosynthetic mechanism exists, by which a structurally unusual HS is synthesized in the mutant cells to fulfill some, but not all, of functions of normal HS.…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 60%
“…In fact, it was reported that mutations in exostosin 1 (EXT1), exostosin 2 (EXT2), [17][18][19] N-deacetylase/N-sulfotransferase 1 (NDST1), N-deacetylase/N-sulfotransferase 2 (NDST2), [20][21][22] heparan sulfate 2-O-sulfotransferase (HS2ST), heparan sulfate 3-O-sulfotransferase-1 (HS3ST1), [23][24][25][26] heparan sulfate 6-O-sulfotransferase-1 (HS6ST1) 27 and heparan sulfate C5 epimerase (GLCE) 28 genes caused serious defects in mice and/or humans. Therefore, a significant decrease in expression of one of these genes might be potentially dangerous for patients.…”
Section: Discussionmentioning
confidence: 99%
“…HS synthesized by mice deficient in N-deacetylase/N-sulfotransferase isoform 1 (NDST-1) is low in N-sulfate, hence in IdoA (sulfated and non-sulfated) and total O-sulfate compared with (20), whereas the overall content of IdoA is similar to that of wild type HS (21). 2 The Hs2st Ϫ/Ϫ mice further show several skeletal abnormalities indistinguishable from those seen in Hsepi Ϫ/Ϫ animals (17,18).…”
Section: Targeted Interruption Of the Glucuronyl C5-epimerase Gene 28364mentioning
confidence: 99%